Comparable Efficacy and Safety of Insulin Glulisine and Insulin Lispro When Given as Part of a Basal–Bolus Insulin Regimen in a 26-Week Trial in Pediatric Patients with Type 1 Diabetes - Philotheou, Areti (Mary Ann Liebert, Inc., 2011)
BACKGROUND: We compared the efficacy and safety of insulin glulisine with insulin lispro as part of a basal–bolus regimen in children and adolescents with type 1 diabetes. METHODS: Overall, 572 children and adolescents (4–17 years old) using insulin glargine or neutral protamine Hagedorn insulin as basal insulin were enrolled in a 26-week, multicenter, open, centrally randomized, parallel-group, noninferiority study. Subjects were randomized to receive glulisine (n = 277) or lispro (n = 295) 0–15 min premeal. RESULTS: Baseline-to-endpoint hemoglobin A1c changes were similar between the two insulins: adjusted mean change (glulisine vs. lispro), 0.10% versus 0.16%; between-treatment difference (glulisine–lispro), &minsu;0.06, 95% confidence interval (−0.24; 0.12); and prespecified noninferiority margin, 0.4%. Overall, for all age groups together, the percentage of patients achieving American Diabetes Association age-specific A1c targets at endpoint was significantly higher (P = 0.039) with glulisine (38.4%) versus lispro (32.0%). From Month 4 to endpoint, both “all” and “severe” symptomatic hypoglycemia rates were similar (3.10 vs. 2.91 and 0.06 vs. 0.07 events/patient-month, respectively). Frequency and type of adverse events, serious adverse events, or hypoglycemia reported as serious adverse events were similar between both groups. CONCLUSIONS: Glulisine was as effective as lispro in baseline-to-endpoint A1c change, and both treatments were similarly well tolerated.